Application of Ergonomics in Product Design Based on Computer-Aided Design. (31st August 2022) - Wu, Changsong
Abstract : At present, China's social economy has entered a new state of normalized development. Since green economy is the strategic goal pursued by sustainable economic development and the core development trend of the economy, industrial product design focuses on design humanization and green production above. The principle of ergonomics is applied in the design of industrial products, which has the function of optimizing the scientificity of industrial products, which makes industrial products more humanized. This paper firstly analyzes the basic concept of ergonomics, then expounds the thinking of ergonomics in industrial product design, and expounds the specific application of ergonomics in industrial product design.